Programs of secondary teacher education in Nepal and the University of the Philippines - Raya, Bishnu Charan 1929- (1970)
This is a comparative study of the curricula for the preparation of secondary teachers of the College of Education, Nepal and the College of Education, University of the Philippines with particular reference to the objectives, the contents of General Education, the contents of Professional Education, the major areas of specialization, and student teaching. The survey method and interview were used in the study to gather data.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Keywords: Teachers, Training of -- Nepal; Teachers, Training of -- Philippines